EKSISTENSI TEATER GARDA ANAK BANGSA INDONESIA ’91 - Rillo Abyudaya; Yunani Yunani; Syarifuddin Syarifuddin (Program Studi Sejarah Peradaban Islam UIN Raden Fatah Palembang, 1970)
GABI'91 Theater Student Activity Unit (Indonesian National Children's Guard Theater Student Activity Unit'91) is a student organization that was founded in 1991, at first the GABI'91 Theater UKM named Teater GABI (Indonesian Children's Association) was a theater formed by Study Program students. Indonesian Language and Literature Education on 21 October 1991. The foundation for the formation of the GABI Theater is as a facility or a forum for students of the Indonesian Language and Literature Study Program to practice and be creative together. The purpose of this research is useful to see how the development and role of Teater Gabi. The analysis process of this research uses the historical method in the form of an investigation that is carried out critically of the conditions, developments, and experiences that have been passed in the past and weighs carefully about a validation of historical sources and interpretations of the sources used. The results of the research conclude that the development of Theater is still active as an activity unit which becomes a forum for students to build and channel their creativity. Not only limited to students, UKM Teater GABI'91 also plays an active role in building the creativity of the community, regional and even national theater activists with their activities.